Prediction of Airfoil Icing and Evaluation of Hot Air Anti-Icing System Effectiveness Using Computational Fluid Dynamics Simulations - Yifan Niu; Zhiqiang Wang; Jieyao Su; Jiawei Yao; Hainan Wang (Aerospace)
Icing poses a serious threat to flight safety, and ice accretion simulations are essential for addressing aircraft icing problems. In ice accretion prediction, systematic research covering all icing conditions based on actual flight phases is lacking, and the performance of anti-icing systems has not been investigated. In this study, maximum ice thickness prediction models for airfoils considering all flight phases were developed, and the performance of hot air anti-icing systems was analyzed. A hot air anti-icing system model was established, and the anti-icing effectiveness of the system under severe icing conditions was evaluated via conjugate heat transfer (CHT) calculations. The calculation results showed that during climbing above 10,000 ft under glaze ice conditions, the maximum ice thickness reached 13.47 mm at −6 °C, with a median volumetric diameter (MVD) of 20 μm. Under rime ice conditions, the maximum thickness exhibited linear relationships with the icing parameters, remaining below 5 mm. The calculation results revealed nonlinear relationships between maximum ice thickness on the airfoil leading edge and the icing conditions. Ice thickness models were established via polynomial regression. The maximum ice thickness data were classified, and 15 regression models were obtained. The relative errors between the predicted and calculated values remained below 3%, demonstrating high predictive accuracy. These models were employed to estimate the effectiveness of piccolo tube hot air anti-icing systems under the most severe icing conditions. The results indicated that 100% anti-icing efficiency was achieved at high ambient temperatures (above −10 °C). During takeoff, holding, and climbing phases with a high speed of 154.3 m/s, the system may face challenges in maintaining anti-icing protection, resulting in runback ice with a maximum thickness exceeding 5 mm.